2021
DOI: 10.1038/s41420-021-00414-2
|View full text |Cite
|
Sign up to set email alerts
|

Lithium as a possible therapeutic strategy for Cornelia de Lange syndrome

Abstract: Cornelia de Lange Syndrome (CdLS) is a rare developmental disorder affecting a multitude of organs including the central nervous system, inducing a variable neurodevelopmental delay. CdLS malformations derive from the deregulation of developmental pathways, inclusive of the canonical WNT pathway. We have evaluated MRI anomalies and behavioral and neurological clinical manifestations in CdLS patients. Importantly, we observed in our cohort a significant association between behavioral disturbance and structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…Hyperactive Wnt signaling leading to increased frequency of myeloid progenitors was shown in Nipbl-depleted zebrafish, and in this study, treatment with the Wnt inhibitor indomethacin ameliorated this phenotype [159]. Lithium, another GSK3 inhibitor, rescued cell proliferation defects in a Drosophila CdLS model and in lymphoblastoid cell lines from CdLS patients [158]. Lithium and other GSK3 inhibitors have been shown be effective inhibitors in several cancers; however, further studies will be required to understand how Wnt agonism could be of therapeutic value in cohesin mutant cells.…”
Section: Targeting Signaling Pathwayssupporting
confidence: 60%
See 1 more Smart Citation
“…Hyperactive Wnt signaling leading to increased frequency of myeloid progenitors was shown in Nipbl-depleted zebrafish, and in this study, treatment with the Wnt inhibitor indomethacin ameliorated this phenotype [159]. Lithium, another GSK3 inhibitor, rescued cell proliferation defects in a Drosophila CdLS model and in lymphoblastoid cell lines from CdLS patients [158]. Lithium and other GSK3 inhibitors have been shown be effective inhibitors in several cancers; however, further studies will be required to understand how Wnt agonism could be of therapeutic value in cohesin mutant cells.…”
Section: Targeting Signaling Pathwayssupporting
confidence: 60%
“…Wnt signaling: Dysregulation of Wnt signaling as an underlying event in cohesin depleted cells has emerged from several studies [80,158,159,185]. We found that cohesin mu-tant MCF10A cells showed increased sensitivity to the glycogen synthase kinase 3 (GSK3) inhibitor LY209031, which stimulates Wnt signaling.…”
Section: Targeting Signaling Pathwaysmentioning
confidence: 99%
“…WNT signaling alterations have been associated with a plethora of CNS abnormalities and canonical WNT pathway was found to be perturbed in CdLS models [ 32 , 33 , 34 , 35 ]. In the contest of embryonic development, the WNT signaling plays a fundamental role in all steps of development by regulating cell proliferation, differentiation, migration, genetic stability and apoptosis, as well as by maintaining adult stem cells and pluripotent state [ 36 ].…”
Section: Biological Basis Of Cdlsmentioning
confidence: 99%
“…The disruption of gene regulation during critical steps of early embryonic development contributes to a WNT signaling alterations that has been associated with a plethora of CNS abnormalities. To date, different studies have shown that the WNT canonical pathway is altered in CdLS models [ 32 , 33 , 34 , 35 ], suggesting it and its downstream effectors as a treatment target option.…”
Section: From Biological Basis To Future Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation